Media Effectiveness Analysis Flipbook Digital Material Mocktail - Rahmah, Rizka Putri Aulia; Febriana, Rina; Yulianti, Yeni (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effectiveness of using digital flipbook media to teach mocktails. This research uses a quasi-experimental method with a non-equivalent control group design. The study sample was a class of culinary students in the 10th grade at SMK Negeri 27 Jakarta, who were divided into two groups: an experimental group and a control group. This study collected data using pre- and post-tests, response questionnaires, and observations. The data were analyzed using univariate, bivariate, and knowledge improvement tests. The univariate test results for the control group obtained a t-count value of 9.78 > t-table 2.05, and the experimental group obtained a t-count value of 16.47 > t-table 2.05. This indicates that there was an increase in knowledge in each group before and after the intervention. The bivariate test results showed a t-count value of 8.18 > t-table 2.00, indicating a difference in the average increase in knowledge. Additionally, the N-gain score was 40% for the control group and 70% for the experimental group. Therefore, it can be concluded that students using digital flipbooks increased their knowledge more than students using PowerPoint media. The results of the response questionnaires for students and observers were also good, at 91% and 96%, respectively. This means that students and observers agreed that digital flipbook media effectively increased students' knowledge. Based on these results, it can be concluded that using digital flipbook media for mocktail material increases students' knowledge of hospitality.